Geochemistry characteristics and emplacement mechanism of the Cenozoic magma in Baoxingchang area, Yunnan Province, SW China. Issue 1 (September 2020) - Dao, Yan; Jian, Long; Zhang, Yourong; Xiao, Gaoqiang; Xu, Shengchao
Abstract: Alkali-rich intrusions associated with Cu-Mo mineralization in Baoxingchang district, displaying both felsic and mafic rock series, can be: divided into four evolution stages. LA-ICP-MS zircon U-Pb ages of the four stages intrusions 36.5∼34.6Ma, 38.0∼33.5Ma, 36.0∼34.5Ma and 34.0Ma, respectively. All the studied rocks have similar magma sources and tectonic setting. The εHf ( t ) values indicate that they were reworked by ancient lithospheric mantle and crustal materials via subduction. Formation of the alkaline-rich intrusions in Baoxingchang area may be involved in the processes of partial melting of mantle rocks, crust-mantle materials and fractional crystallization. It appears an increasing tendency from felsic intrusions, to enclaves and then to early-stage lamprophyre to late-stage lamprophyre.